Location of plasmid-mediated citrate utilization determinant in R27 and incidence in other H incompatibility group plasmids. - Taylor, D E (1986)
Citrate utilization (Cit+) is encoded by a specific subgroup of incompatibility HI plasmids, viz., IncHI1 plasmids. Only one IncHI1 plasmid, pRG1271, which originated in a Mexican typhoid outbreak in 1972, did not specify Cit+. All other Cit+ plasmids hybridized to a Cit+ probe, a 2-kilobase BglII fragment derived from the Cit+ transposon Tn3411. The position of the Cit+ determinant was mapped to a 13.5-kilobase ApaI fragment within the prototype IncHI1 plasmid R27. No other functions have been mapped within this region. Citrate utilization mediated by IncHI1 was observed only after a prolonged lag period of approximately 150 h, and certain Escherichia coli strains, e.g., E. coli K-12 J53-1, were not able to utilize citrate specified by the H plasmids. Most E. coli strains harboring the multicopy Cit+ plasmid pOH2, a derivative of pBR322, required only 18 to 24 h to express the Cit+ phenotype, but E. coli J53-1 (pOH2) required at least 72 h for expression.